QuickAid Heroes: Game Edukatif Berbasis Android untuk Meningkatkan Keterampilan Melakukan First Aid Pada Remaja - Andriani, Rizki; Apriani, Fitri; Nasution, Nurromsyah (Media Karya Kesehatan, 2025)
Accidents and accidental injuries are more likely to occur in adolescents who tend to be active and like challenges, so there is a risk of high morbidity and mortality rates among adolescents globally. The number of injuries in adolescents in Indonesia is high, partly due to a lack of skills in performing first aid (first aid). These skills are essential for reducing the risk of death and preventing disability, as well as empowering adolescents to keep themselves and others safe. According to initial interviews, adolescents have been taught simple first aid and received education from various institutions, such as treating wounds and handling fever. However, they often do not implement this knowledge and feel unsure or unprepared when facing an emergency, even directly contacting an adult instead of providing first aid so that their skills in performing first aid are still not optimal, as evidenced by panicked reactions during emergencies. This community service activity aims to optimize education and first aid skills through an Android-based educational game media called QuickAid Heroes. The implementation method is used through five stages: program socialization and training, including first aid education, application of technology through android-based educational games, mentoring, and evaluation related to the actions taken and the program's sustainability. The results obtained from this activity are in the form of an increase in first aid skill scores after adolescents are introduced to the QuickAid Heroes game and partners' commitment to optimize adolescents' ability to do first aid on a regular basis. This shows that the skill of doing first aid can be optimized; one of the ways is through the Android-based educational game Quick Aid Heroes. It is recommended that related parties continuously allocate time regularly for first aid education for all adolescents